Promotion Mechanisms of Stromal Cell-Mediated Lung Cancer Development Within Tumor Microenvironment - Wu S; Hu Y; Sui B (Cancer Management and Research)
Siyu Wu,1,* Yumeng Hu,1,* Bowen Sui2 1Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of China; 2First Affiliated Hospital, Heilongjiang University of Chinese Medicine, Harbin, People’s Republic of China*These authors contributed equally to this workCorrespondence: Bowen Sui, Email suibowen79@126.comAbstract: Lung cancer, with its high incidence and mortality rates, has garnered significant attention in the medical community. The tumor microenvironment (TME), composed of tumor cells, stromal cells, extracellular matrix, surrounding blood vessels, and other signaling molecules, plays a pivotal role in the development of lung cancer. Stromal cells within the TME hold potential as therapeutic targets for lung cancer treatment. However, the precise and comprehensive mechanisms by which stromal cells contribute to lung cancer progression have not been fully elucidated. This review aims to explore the mechanisms through which stromal cells in the tumor microenvironment promote lung cancer development, with a particular focus on how immune cells, tumor-associated fibroblasts, and endothelial cells contribute to immune suppression, inflammation, and angiogenesis. The goal is to provide new insights and potential strategies for the diagnosis and treatment of lung cancer.Keywords: tumor microenvironment, lung cancer, stromal cells, immune cells, cancer-associated fibroblasts, endothelial cells